First-principle study of Ti50Ni50-xNbx shape memory alloys for biomedical applications - Mathews Thabiso; Madigoe Mandy; Modiba Rosinah; Sithole Enoch (MATEC Web of Conferences)
The excellent shape memory effect and biocompatibility of TiNi alloys have revolutionized the scientific and industrial communities, particularly in biomedical applications. These materials can undergo major or quasi-plastic deformation before returning to their original form when subjected to external stimuli like stress or temperature. However, nickel has been shown to be carcinogenic, it may lead to cytotoxicity which can result in infections, follow-up issues, or implant failure. The aim of this study is to improve the biocompatibility of TiNi by substituting Ni with Nb employing the first principle approach. The structural and elastic properties of the TiNi- Nb alloy were investigated using the CASTEP code embedded in Materials Studio. The findings indicated that Ti8Ni4Nb4's formation energy had increased. The poisons ratio decreased slightly, reaching a value of 0.32 in line with the G/B findings. Increasing Nb content also lowered the density of states at the Fermi levels. It was found that Ti8Ni4Nb4 was the most suitable substitute for TiNi alloys.